The Satisfaction of Tourists on Community-based Tourism in My Hoa Hung, Vietnam - Thai Huynh Phuong Lan; Nguyen Thi Thanh Truc (Universitas Andalas, 2021)
The research was conducted to assess the satisfaction of tourists with local community-based tourism services in the My Hoa Hung (MHH) commune in Long Xuyen, An Giang, Vietnam. The research findings will be the scientific and practical basis for effective and sustainable tourism development in MHH. A mixed-method of qualitative and quantitative is used in this study. Tourist local officers and tourist providers were interviewed as key informants. Such samples of domestic and foreign tourists were interviewed using a questionnaire survey to collect and analyze the tourists' satisfaction with tourism services. The result shows that tourists visiting MHH come from different regions and countries, from different age groups, and occupations, so their needs and satisfaction with MHH's community-based tourism services are also very diverse. The study uncovers that tourists are most satisfied with the human factor, especially the enthusiasm attitude of the tourist service provider (reaching 4.07 points), and then environmental landscape (3.90 points), infrastructure (3.90 points), price (3.80 points), and the lowest security- safety factor (3.73 points). However, in each factor, there are still a number of criteria that tourists are not satisfied with, which should be paid attention to for sustainable tourism development, such as environmental sanitation, traffic safety, and English communication ability of tourists' service providers.